1991
DOI: 10.1136/gut.32.9.983
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity at work and duodenal ulcer risk.

Abstract: To determine whether the social class differences in duodenal ulcer frequency may be explained by differences in physical activity at work, the energy expenditure during work, smoking habits, and social class were compared in 76 recently diagnosed duodenal ulcer patients and in age and sex matched community controls. As anticipated, the relative risk of duodenal ulcer showed significant associations with smoking and social class. Social class and physical activity at work were associated with one another. Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Psychologic stress is likely to be important in traditional peptic ulcers, whether related to H pylori or NSAIDs. This effect is likely related to an increase in acid secretion, which enhances the aggressive factors in someone predisposed to peptic ulcer or exacerbates preexisting peptic ulcer by increasing the duodenal acid load [71][72][73].…”
Section: • Master the Hanging Comparative (''Better'' But Better Thamentioning
confidence: 99%
“…Psychologic stress is likely to be important in traditional peptic ulcers, whether related to H pylori or NSAIDs. This effect is likely related to an increase in acid secretion, which enhances the aggressive factors in someone predisposed to peptic ulcer or exacerbates preexisting peptic ulcer by increasing the duodenal acid load [71][72][73].…”
Section: • Master the Hanging Comparative (''Better'' But Better Thamentioning
confidence: 99%
“…The most recent analysis [45] found that even after adjusting for the covariates of age, smoking habits and social class, the risk of a recent diagnosis of duodenal ulcer was 1.3 for those who were engaged in moderate physical work, and 3.6 for individuals with a high level of occupational activity.…”
Section: Occupational Activitymentioning
confidence: 96%
“…The recurrence rate of gastric consumed alcohol and used NSAIDS. Katschinski et al [20] conducted study in 76 recently diagnosed ulcer patients. It was seen that the risk of physically active work was associated with duodenal ulcer, with relative risk for moderate-and high-activity compared with sedentary work being 1.3 (0.6-30) and 3.6 (1.…”
Section: Vol 3 | Issue 1 | Jan-mar 2012 Chronicles Of Young Scientistsmentioning
confidence: 98%